PERSEPSI DAN REAKSI GENERASI Z TERHADAP FENOMENA GENDER FLUID DAN GAYA FESYEN ANDROGINI - Brigitta Cheria Belinda (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
ABSTRACT The phenomenon of gender fluid and androgynous fashion style indeed exists and is rife in society. Until now this phenomenon is still receiving a lot of different perceptions and reactions from the community. The purpose of this research is to find out Generation Z's understanding of the gender fluid phenomenon through the concept of androgynous fashion style on Instagram communication media and Generation Z's reactions and perceptions of this phenomenon. Data collection is done by documentation, observation, interviews, and focus group discussions. This research is a qualitative research with descriptive methods. The results of the study show that many definitions given by Generation Z are still unclear but their understanding has begun to appear. Generation Z has different perceptions and reactions to this phenomenon. There are perceptions and reactions that are neutral,negative and positive. Even so, Generation Z has sufficiently accepted the phenomenon of gender through the concept of androgynous fashion style. Key Word: Androgynous Fashion Style, Gender fluid, Generation Z, Perception, Reactions